In Situ Observation of Electron Acceleration by a Double Layer in the Bow Shock - C. M. Wang; S. Y. Huang; Z. G. Yuan; K. Jiang; J. Zhang; Y. Dong; Q. Y. Xiong (The Astrophysical Journal, 2023)
The importance of the electric potential along the field direction in the acceleration of electrons in the quasi-perpendicular bow shock has been proposed. Nevertheless, the mechanism by which electrons are accelerated in the bow shock remains unclear from the perspective of in situ observation. In this study, utilizing data obtained by the Magnetospheric Multiscale mission, we identify a double layer (DL) located within the transition layer of the quasi-perpendicular bow shock. It is found that the electric potential generated by this DL corresponds well with an increase in electron parallel temperature, suggesting that the DL can effectively accelerate the electrons in the bow shock. Furthermore, strong whistler emissions have been detected in the vicinity of this DL. It seems that the electrons accelerated by the DL could potentially supply the necessary free energy to excite the observed whistler waves. Thus, the presence of whistler waves provides indirect evidence of an electron beam generated by the DL in bow shock. Our observations demonstrate that the DL can accelerate electrons effectively and impact the electron dynamics within the bow shock.